Good long‐term outcome of Budd‐Chiari syndrome with a step‐wise management12. Issue 5 (22nd April 2013) - Seijo, Susana; Plessier, Aurelie; Hoekstra, Jildou; Dell'Era, Alessandra; Mandair, Dalvinder; Rifai, Kinan; Trebicka, Jonel; Morard, Isabelle; Lasser, Luc; Abraldes, Juan G.; Darwish Murad, Sarwa; Heller, Jörg; et al.
Abstract: Budd‐Chiari syndrome (BCS) is a rare, life‐threatening disease caused by obstruction of hepatic venous outflow. The aim of the study was to assess long‐term outcome and identify prognostic factors in BCS patients managed by a step‐wise approach using anticoagulation, angioplasty/thrombolysis, transjugular intrahepatic portosystemic shunting (TIPS), and orthotopic liver transplantation (OLT). We reviewed long‐term data on 157 patients previously included by the European Network for Vascular Disorders of the Liver, a multicenter prospective study of newly diagnosed BCS patients in nine European countries. Patients were followed for a median of 50 months (range, 0.1‐74.0). During the study, 88 patients (56%) received at least one invasive intervention (22 patients angioplasty/thrombolysis, 62 TIPS, and 20 OLT) and 36 (22.9%) died. Most interventions and/or deaths occurred in the first 2 years after diagnosis. The Rotterdam score was excellent in predicting intervention‐free survival, and no other variable could significantly improve its prognostic ability. Moreover, BCS‐TIPS prognostic index (PI) score (based on international normalized ratio, bilirubin, and age) was strongly associated with survival and had a discriminative capacity, which was superior to the Rotterdam score. Conclusions: The current study confirms, in a large cohort of patients with BCS recruited over a short period, that a step‐wise treatment approach provides good long‐term survival. In addition, the study validates the Rotterdam score for predicting intervention‐free survival and the BCS‐TIPS PI score for predicting survival. (HEPATOLOGY 2013;)